Yellow Nail Syndrome: A Review Article. Issue 6 (November 2016) - Woodfield, Georgia E.; Loebinger, Michael R.; Wilson, Robert
Abstract : Yellow nail syndrome is a rare clinical syndrome characterized by a triad of yellow dystrophic nails, lymphedema, and respiratory manifestations. These include chronic cough with sputum production, recurrent respiratory infections, pleural effusions, bronchiectasis, and rhinosinusitis. This paper reviews the literature on this rare condition, aiming to increase awareness of this disease to allow better diagnosis, management, and patient outcomes.